Ground State Lifetime of Strong-Coupled Polaron in an Asymmetric Quantum Dot (Journal of Atomic and Molecular Sciences, 2018)
On the condition of electron and LO-phonons strong-coupled, the ground-stateenergy of polaron has been obtained by using linear combination operator and unitarytransformation methods in an asymmetric quantum dot. Quantum transition which causesthe changes of the polaron lifetime is occurred in the quantum system due to the electron-phonon interaction and the influence of external temperature effect which is the polaronleap from the ground-state to the first-excited state absorbing a LO-phonon. Numericalcalculation is performed and the results show that the ground-state lifetime of polaron increases with increasing the ground-state energy and decreases with increasing the coupling-strength. The ground-state lifetime is extended with the shortening of the temperature. It isalso observed that the ground-state lifetime is a decreasing function of the transverse andlongitudinal confinement lengths of the quantum dot.
Keywords: asymmetric quantum dot; strong-coupled; ground-state lifetime; polaron.